Ray-based inversion accounting for scattering for biomedical ultrasound tomography. (13th October 2021) - Javaherian, Ashkan; Cox, Ben
Abstract: An efficient and accurate image reconstruction algorithm for ultrasound tomography in soft tissue is described and demonstrated, which can recover accurate sound speed distribution from acoustic time series measurements. The approach is based on a second-order iterative minimisation of the difference between the measurements and a model based on a ray-approximation to the heterogeneous Green's function. It overcomes the computational burden of full-wave solvers while avoiding the drawbacks of time-of-flight methods. Through the use of a second-order iterative minimisation scheme, applied stepwise from low to high frequencies, the effects of scattering are incorporated into the inversion.